2020
DOI: 10.1002/eap.2221
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis can guide resilience‐based management in forest landscapes under global change

Abstract: Network analysis can guide resilience-based management in forest landscapes under global change. Ecological Applications 00(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 100 publications
2
34
0
2
Order By: Relevance
“…Similar transitions from boreal forest to open parklands or prairie ecosystems is also projected for several regions in western Canada as a result of increase drought and wildfire activity (Stralberg et al 2018). Diversified forests were shown to be more resilient under increased anthropogenic climate forcing (Duveneck et al 2014; Mina et al 2020). Higher species diversity along with diversified functional traits and low projected disturbance rates will help northern hardwood forest landscapes being more resilient to climate-induced changes although species turnover will likely occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar transitions from boreal forest to open parklands or prairie ecosystems is also projected for several regions in western Canada as a result of increase drought and wildfire activity (Stralberg et al 2018). Diversified forests were shown to be more resilient under increased anthropogenic climate forcing (Duveneck et al 2014; Mina et al 2020). Higher species diversity along with diversified functional traits and low projected disturbance rates will help northern hardwood forest landscapes being more resilient to climate-induced changes although species turnover will likely occur.…”
Section: Discussionmentioning
confidence: 99%
“…Harvest-induced increases in disturbance rates might modify the system’s inertia and accelerate climate-induced changes by removing resident communities and providing resources for warmed-adapted establishment and growth (Steenberg et al 2013; Brice et al 2020). Indeed, it was shown that alike canopy gaps (Leithead et al 2010), moderate harvest-induced disturbance rates under warmer temperatures could favor co-occurring thermophilous pioneer but also shade-tolerant species, and hasten their northward migration within the boreal forest (Steenberg et al 2013; Brice et al 2019, 2020; Mina et al 2020). When cumulated with increasing natural disturbance rates, harvest could bring total disturbance rates outside their range of natural variability (Bergeron et al 2006; Cyr et al 2009), resulting in regeneration failures and long-term changes in successional pathways (Splawinski et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology could be further improved by considering additional local yield tables and observations. Nevertheless, by documenting such correspondence rules the model inputs generation is significantly more transparent and reproducible than other LANDIS-II studies (e.g., Mina et al, 2021).…”
Section: Spatial Imputation and Initial Vegetation Conditionsmentioning
confidence: 92%
“…PnET-Succession requires a series of generic, ecoregionand species-specific parameters. Although many default values have been made available by the model developers and in past application studies, most parameters require calibration according to the biogeographical location of the target landscape and the tree species included in the simulations (McKenzie et al, 2019;Mina et al, 2021).…”
Section: Model Descriptionmentioning
confidence: 99%